Quark-gluon plasma phenomenology from anisotropic lattice QCD - RYAN, SINEAD (My University, 2016)
The FASTSUM collaboration has been carrying out simulations of N f = 2 + 1 QCD at nonzero temperature in the fixed-scale approach using anisotropic lattices. Here we present the status of these studies, including recent results for electrical conductivity and charge diffusion, and heavy quarkonium (charm and beauty) physics.
AIP Conference Proceedings
PUBLISHED
Cited By :1 Export Date: 6 January 2017
Keywords: FASTSUM collaboration; FASTSUM collaboration